Succesfull Learning in the Middle of Pandemic COVID-19 - Windi Setiawan (PROCEEDING UMSURABAYA, 2020)
Abstract. COVID 19 Has become an epidemic that changes the way of human life. Startingfrom small things so that we care more about our health. Like washing hands before and after doing activities, to wear a mask when leaving the house. Not only that, but COVID-19 has also demanded that we stay away from the crowd and keep our distance. This situation results in an educational policy implemented in the network (e-learning). However, please note that the implementation of e-learning has not run optimally. Several obstacles result in learning not going as expected. Such as, teachers who must quickly change the learning system, students who stammer for so many tasks, and parents who are increasingly stressed in accompanying their children in learning material delivered by teachers through elearning. Through this paper the author wants to convey any obstacles that occur in the field during e-learning takes place, how to resolve these obstacles, and what applications are easy to use by teachers, parents, and students in the success of learning during a COVID 19 pandemic supported by the results of research that has been there is..